Distant Voices, Still Cinema? Around the Movies (Cinéma & Cie. Film and Media Studies Journal, 2014)
The contribution deals with the contemporary production of neorealist films and photo-romances, a kind of illustrated magazine deploying sentimental narratives through drawings, or mostly stills. Both products were genuinely Italian and marked the country’s post-war culture. Whereas the first was advocated as highbrow art and the most remarkable expression of the nation in times of hardship, the latter has been disregarded as cheap popular culture; just in recent times it received the attention that a mass phenomenon deserves. What has been overlooked or only briefly discussed are shared areas between the two. The article tackles three issues: how neorealism partook in and merged into post-war visual culture, to the point that some thresholds and boundaries between highbrow, politically conscious and aesthetically experimental films and formulaic cultural products are hard to detect; the role of intertextuality in this process; and what happened in the transformation that occurred along the passage from the screen to the magazine, by comparing the function narratives had in novelization and in films.